Corynebacterium Bone and Joint Infection (BJI): A Retrospective Cohort Study in a Reference Center for BJI Management. (4th October 2017) - Ferry, Tristan; Chauvelot, Pierre; Triffault-Fillit, Claire; Braun, Evelyne; Perpoint, Thomas; Laurent, Frederic; Fessy, Michel-Henri; Lustig, Sébastien; Chidiac, Christian; Valour, Florent; ,
Abstract: Background: Corynebacterium is a rare etiologic agent of BJI. We aimed to describe this rare clinical condition and to assess treatment failure determinants. Methods: All adult patients with proven Corynebacterium BJI (i.e., consistent clinical/radiological signs, AND ≥2 reliable positive bacteriological samples, AND treated as such) were included in a retrospective cohort study. After cohort description, determinants of treatment failure (i.e., infection persistence, relapse, requirement of additional surgical procedure, and BJI-related death) were determined using stepwise logistic regression and Kaplan-–Meier curve analysis. Results: The 51 included BJI were more frequently chronic (88.2%), orthopaedic device related (ODI, 74.5%) and polymicrobial (78.4%). Surgery was performed in 92.2% of cases, and considered as appropriate in 76.5% of them. The main first-line antimicrobials were glycopeptides (68.6%), β-lactams (50%), and/or clindamycin (10.0%). Three (5.9%) patients received daptomycin as part of first-line regimen, and 8 (15.7%) at any point of treatment. After a follow-up of 60.7 (IQR 30.1–115.1) weeks, 20 (39.2%) treatment failures were observed, including 4 (20%) Corynebacterium -documented relapse. Independent risk factors were initial biological inflammatory syndrome (OR 16.1; P = 0, 030) and inappropriate surgical management (OR 7.481; P = 0.036). Interestingly, all patients receiving daptomycin as part of first-line regimen failed ( P < 0.001), including one patient with a Corynebacterium -documented relapse with a daptomycin increased MIC. Among patients with ODI, survival curve analysis disclosed a worst prognosis in case of prosthetic joint infection ( P = 0.030), unappropriate surgical management ( P = 0.029) and daptomycin use as first-line regimen ( P < 0.001). Conclusion: Corynebacterium BJI is a poorly known condition, frequently chronic, and polymicrobial. An important rate of failure was observed, associated with inappropriate surgical management and daptomycin use as part of first-line regimen. As described for other clinical conditions such as infective endocarditis, daptomycin should be avoid or used in combination therapy to prevent resistance selection and treatment failure. Disclosures: T. Ferry, HERAEUS: Consultant, Speaker honorarium. S. Lustig, Heraeus: Consultant, Consulting fee